2018
DOI: 10.29252/ijrm.16.10.623
|View full text |Cite
|
Sign up to set email alerts
|

Body fat percentage is a better marker than body mass index for determining inflammation status in polycystic ovary syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is an endocrinopathic disorder most commonly experienced by women of reproductive age, and it is characterized by a low-grade chronic inflammatory condition. Excessive fat deposit has been long considered as an etiological factor in the pathogenesis of this inflammatory condition. Currently, body mass index (BMI) or percentage of body fat is used as a marker to assess the body fat composition of a person. Objective: To determine whether BMI or body fat percentage (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Studies investigating body composition by BIA reported that in PCOS women higher metabolic dysfunction was associated with higher fat mass (FM) and fat-to-lean mass ratio as compared to controls [22]. In addition, body fat percentage was positively associated with levels of inflammatory biomarkers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating body composition by BIA reported that in PCOS women higher metabolic dysfunction was associated with higher fat mass (FM) and fat-to-lean mass ratio as compared to controls [22]. In addition, body fat percentage was positively associated with levels of inflammatory biomarkers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS), an endocrine disorder affects approximately 14-19% % of women in reproductive age [1]. PCOS has been associated with low-grade inflammation based on increased levels of several inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…One of the theories says that ovarian polycystic syndrome is a condition of chronic inflammation in low degree. 5 There are several markers that can be used to measure inflammation, including CRP, Neutrophil to Lymphocyte Ratio (NLR), Platelet Lymphocyte Ratio (PLR), and monocyte/HDL ratio. Complete blood count is an inexpensive, routine, and feasible test that may provide information regarding the red blood cells, white blood cells, and platelets.…”
Section: Introductionmentioning
confidence: 99%